Study on serum zinc and copper levels in pulmonary tuberculosis patients before starting Directly Observed Treatment, Short-course (Mediscope, 2021)
Background: Tuberculosis is a major public health concern throughout the world including Bangladesh. The prevalence of tuberculosis (TB) is increasing day by day. Around one-third of world population is infected with M. tuberculosis. Still pulmonary tuberculosis (PTB) remains one of the important causes of mortality throughout the world with economic burden.Objective: To evaluate levels of the serum zinc and serum copper in smear positive PTB patients before starting Directly Observed Treatment, Short-course (DOTs) therapy.Methods: This was a cross-sectional type of observational study. A total of 100 subjects were included in this study. Among them 50 were smear positive PTB patients denoted as case group and 50 were apparently healthy individuals denoted as control group. Biochemical tests were carried out in the department of biochemistry of Mymensingh Medical College, Mymensingh. All the statistical analyses were performed by using SPSS version 21. Results were evaluated by using Student’s t-test.Results: After careful evaluation there was significant decrease in serum zinc level along with significant increase in serum copper level among the case group when compared with the control group. The mean values of serum zinc level were 93.96±10.04 μg/dl and 72.84±7.73 μg/dl in control and case group respectively. Serum zinc level decreased significantly (p